The use of clinical cases as a type of medical text in teaching professional communication in English - Israilov , Jakhongirkhon (The Lingua Spectrum, 2025)
The article explores case reports as a genre of authentic medical texts with high didactic potential for teaching English to medical university students. It emphasizes that a case report is a logically structured, functionally relevant type of text closely aligned with real-life clinical practice, making it an effective tool for developing both linguistic and cognitive competencies. Working with case reports enhances academic writing, text analysis, interpretation and generalization skills, while also reinforcing professional vocabulary acquisition through contextual learning. Moreover, this genre allows students to simulate communicative situations typical of future medical practice, such as explaining diagnoses, discussing treatment strategies, and presenting arguments in professional dialogue. The article outlines the stages of integrating case reports into the educational process, including material selection and adaptation, task types (reading, writing, discussion), as well as interactive learning elements. The practical outcomes of implementing this method are also discussed, highlighting its effectiveness in the context of teaching medical English in higher education.